2012
DOI: 10.1186/1477-7819-10-242
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AQP5 and AQP8 in human colorectal carcinoma and their clinical significance

Abstract: BackgroundThe aquaporins (AQPs) are a family of small membrane transport proteins whose overexpression has been implicated in tumorigenesis. However, the expression of AQP5 and AQP8 in colorectal cancer and the clinical significance remain unexplored. This study aimed to detect the expression of AQP5 and AQP8 in clinical samples of colorectal cancer and analyze the correlations of their expression with the clinicopathological features of colorectal cancer.MethodsForty pairs of colorectal cancer tissue and para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 15 publications
5
37
0
Order By: Relevance
“…Huang et al (18) also verified that AQP5 promotes the proliferation and migration of human gastric carcinoma cells. Wang et al (19) performed a study to show that AQP5 was mainly expressed in colorectal carcinoma cells and barely expressed in paraneoplastic normal tissues. The clinical significance of AQP5 in colorectal carcinoma is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (18) also verified that AQP5 promotes the proliferation and migration of human gastric carcinoma cells. Wang et al (19) performed a study to show that AQP5 was mainly expressed in colorectal carcinoma cells and barely expressed in paraneoplastic normal tissues. The clinical significance of AQP5 in colorectal carcinoma is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established that tumor growth, development, invasion and metastasis depend upon sufficient nutrient supply and metabolism, and that water molecules are important in the modulation of the tumor microenvironment and metabolism (9,10). Increasing evidence has demonstrated that aquaporins (AQPs), a family of small transmembrane proteins responsible for water transport, are involved in the incidence and progression of cancer (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…But Jablonski et al (2007) reported that AQP8 expression down-regulated in mouse hepatocellular carcinoma model. AQP8 was mainly expressed in paraneoplastic normal tissues and barely expressed in colorectal carcinoma cells (Wang et al, 2012). These contradictory reports indicate the necessity of further research on effects of AQPs in tumorigenesis.…”
Section: Discussionmentioning
confidence: 98%